BAK1 plays contrasting roles in regulating abscisic acid‐induced stomatal closure and abscisic acid‐inhibited primary root growth in Arabidopsis. Issue 6 (31st May 2022) - Deng, Jinping; Kong, Lingyao; Zhu, Yinhua; Pei, Dan; Chen, Xuexue; Wang, Yu; Qi, Junsheng; Song, Chunpeng; Yang, Shuhua; Gong, Zhizhong
Abstract: The mechanisms that balance plant growth and stress responses are poorly understood, but they appear to involve abscisic acid (ABA) signaling mediated by protein kinases. Here, to explore these mechanisms, we examined the responses of Arabidopsis thaliana protein kinase mutants to ABA treatment. We found that mutants of BRASSINOSTEROID INSENSITIVE 1‐ASSOCIATED RECEPTOR KINASE 1 ( BAK1 ) were hypersensitive to the effects of ABA on both seed germination and primary root growth. The kinase OPEN STOMATA 1 (OST1) was more highly activated by ABA in bak1 mutant than the wild type. BAK1 was not activated by ABA treatment in the dominant negative mutant abi1‐1 or the pyr1 pyl4 pyl5 pyl8 quadruple mutant, but it was more highly activated by this treatment in the abi1‐2 abi2‐2 hab1 ‐ 1 loss‐of‐function triple mutant than the wild type. BAK1 phosphorylates OST1 T146 and inhibits its activity. Genetic analyses suggested that BAK1 acts at or upstream of core components in the ABA signaling pathway, including PYLs, PP2Cs, and SnRK2s, during seed germination and primary root growth. Although the upstream brassinosteroid (BR) signaling components BAK1 and BR INSENSITIVE 1 (BRI1) positively regulate ABA‐induced stomatal closure, mutations affecting downstream components of BR signaling, including BRASSINOSTEROID‐SIGNALING KINASEs (BSKs) and BRASSINOSTEROID‐INSENSITIVE 2 (BIN2), did not affect ABA‐mediated stomatal movement. Thus, our study uncovered an important role of BAK1 in negatively regulating ABA signaling during seed germination and primary root growth, but positively modulating ABA‐induced stomatal closure, thus optimizing the plant growth under drought stress. Abstract : BRASSINOSTEROID INSENSITIVE1‐ASSOCIATED RECEPTOR KINASE negatively regulates abscisic acid (ABA) signaling during seed germination and primary root growth, but positively modulates ABA‐induced stomatal closure, thus optimizing plant growth under drought stress.